New estimates of Australia’s centenarian population - Wilson, Tom; Terblanche, Wilma (International Journal of Population Data Science, 2018)
Introduction The population of Australia at the very highest ages is growing rapidly, like that of many countries. But official population estimates at these ages are of lower quality than those at younger ages, a problem shared by many countries which base their population estimates on census counts. This has implications for many uses of the data, especially rates for which the estimates provide denominators. Objective The aims of this paper are to (1) present new population estimates of Australia’s centenarian population (those aged 100 years and above) for 1981 to 2016 which are better quality than official statistics, and (2) illustrate the utility of such estimates as rate denominators by calculating centenarian death rates. Methods Population estimates at the highest ages were prepared using a combination of the Extinct Cohort method and a modified Survivor Ratio method. The key modifications of the latter involve projecting and smoothing Survivor Ratios within an iterative set of calculations. Death rates were calculated as standard occurrence/exposure rates. Input data of deaths and official Estimated Resident Populations were obtained from the Australian Bureau of Statistics. Results We show that Australia’s centenarian population grew from about 500 in 1981 to just over 3,900 by 2016, equivalent to an annual average growth rate of 5.9%. Centenarian death rates for the 1981-2016 period remained roughly steady, averaging 0.44 for females and 0.51 for males. Conclusions Our modified approach adds a degree of stability to the Survivor Ratio method and yields high-quality population estimates and death rates at advanced ages. It could easily be implemented by national statistical offices.